2009
DOI: 10.4186/ej.2009.13.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Glass Window with Film for Buildings in a Hot Climate

Abstract: This article is about the developing parameters and relationships for selecting a proper glass window applied with film as building envelopes for buildings located in a hot climate based on its thermal performances. Thermal comfort of the occupants sitting near the glass window is the thermal performance that needed to be considered besides the heat transmission in selecting a proper type of glass to use as a glass window for the building. The predicted percentage of dissatisfied (PPD) is chosen as a thermal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
(7 reference statements)
1
11
0
Order By: Relevance
“…Glass windows affect the building by heat transmission and compromised thermal comfort [133][134][135][136][137][138][139] and studies by Chaiyapinunt et al, showed that the thermal comfort was dependent on the optical properties (total transmittance and total absorbance) and the overall heat transfer coefficient of type of glass used in windows [140]. Singh et al, have also studied the impact of different glazing systems on human thermal comfort in an Indian scenario [141].…”
Section: Other Building Componentsmentioning
confidence: 99%
“…Glass windows affect the building by heat transmission and compromised thermal comfort [133][134][135][136][137][138][139] and studies by Chaiyapinunt et al, showed that the thermal comfort was dependent on the optical properties (total transmittance and total absorbance) and the overall heat transfer coefficient of type of glass used in windows [140]. Singh et al, have also studied the impact of different glazing systems on human thermal comfort in an Indian scenario [141].…”
Section: Other Building Componentsmentioning
confidence: 99%
“…NaNO 3 (Neodymium oxide)  Physicochemical Method: These methods depends on the addition of colouring agents which compliment the green colour such as oxides of selenium and cobalt, as well as the oxidation of ferrous oxide to ferric oxide by using oxidative agents such as sodium nitrate [8,9,11,13and14].…”
Section: Treatment Of Green Colour In Glassmentioning
confidence: 99%
“…Although, national studies and reports available [1,2] had shown that raw material from certain districts local causes defects in glass manufactured, specially the presence of green colour as a result of the presence of ferric oxides in limestone used in glass manufacturing. Studies available on the effect of ferric oxides on the presence of green colour in glass [3,4] had shown that increase of ferric oxide content in raw material had increased the presence of green colour, meanwhile this causes decreased in demand for the glass as well as direct effect on the physical properties of glass [5][6][7]. Therefore this research aims to study the effect of green colour on the transmitivity of glass, and study the possibilities of reducing green colour in glass produced, as well as the necessity of finding new quarries for limestone with lower ferrous oxide contents.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce this solar heat gain and maintain thermal comfort for the occupants, air conditioning systems are required. A considerable amount of research has been conducted on thermal performance of glass windows in terms of heat transmission and thermal comfort: Athienitis and Haghighat [1]; Gan [2]; Chaiyapinunt et al [3]; La Gennusa et al [4]; La Gennusa et al [5]; Singh et al [6]; Chaiyapinunt and Khamporn [7]; Dong et al [8]; Hwang and Shu [9] and Khamporn and Chaiyapinunt [10]. However, when a building is actually used, occupants often install venetian blinds as an indoor shading device to reduce glare and maintain privacy.…”
Section: Introductionmentioning
confidence: 99%